Incidence and severity of immune-related hepatitis after dual checkpoint therapy is linked to younger age independent of herpes virus immunity - Zhen Zhang; David Rafei-Shamsabadi; Saskia Lehr; Nico Buettner; Rebecca Diehl; Daniela Huzly; David J Pinato; Robert Thimme; Frank Meiss; Bertram Bengsch (Journal of Translational Medicine, 2022)
Abstract Background and Aims Dual immune checkpoint blockade (ICB) therapy can result in immune-related-adverse events (irAE) such as ICB-hepatitis. An expansion of effector-memory (TEM) CD4 T cells associated with antiviral immunity against herpesviridae was implicated in ICB-hepatitis. Notably, these memory subsets are frequently associated with age. Here, we sought to understand baseline patient, immune and viral biomarkers associated with the development of ICB-hepatitis to identify currently lacking baseline predictors and test if an expansion of TEM or positive serology against herpesviridae can predict ICB-hepatitis. Methods A discovery (n = 39) and validation cohort (n = 67) of patients with advanced melanoma undergoing anti-PD-1&anti-CTLA4 combination therapy (total n = 106) were analyzed for baseline clinical characteristics, occurrence of irAE and oncological outcomes alongside serological status for CMV, EBV and HSV. Immune populations were profiled by high-parametric flow cytometry (n = 29). Results ICB-hepatitis occurred in 59% of patients within 100 days; 35.9% developed severe (CTCAE 3–4) hepatitis. Incidence of ICB-hepatitis was higher in the younger (< 55y: 85.7%) compared to older (> = 55y: 27.8%) age group (p = 0.0003), occured earlier in younger patients (p < 0.0001). The association of younger age with ICB-Hepatitis was also observed in the validation cohort (p = 0.0486). Incidence of ICB-hepatitis was also associated with additional non-hepatic irAE (p = 0.018), but neither positive IgG serostatus for CMV, EBV or HSV nor TEM subsets despite an association of T cell subsets with age. Conclusion Younger age more accurately predicts ICB-hepatitis after anti-PD-1&anti-CTLA4 checkpoint therapy at baseline compared to herpes virus serology or TEM subsets. Younger patients should be carefully monitored for the development of ICB-hepatitis.